Pengaruh Dukungan Sosial dan Efikasi Diri terhadap Subjective Well Being pada Pasien Kanker Payudara Pasca Mastektomi - Robertus Surjoseto; Devy Sofyanty (Lembaga Pengembangan Kinerja Dosen, 2023)
Breast cancer is still a major health problem for women around the world, then incidence of this disease continues to increase in recent years in various parts of the world. Breast loss which came from mastectomy became main problem in people’s body image. Breasts cancer can cause patients to experience changes in aspects of quality of life which include physical health, psychological well being, social relationships and the environment. This research amis to examine and analyze influence social support and self efficacy on the subjective well being in breast cancer patients post mastectomy at oncology surgery clinic dr.Cipto Mangunkusumo Hospital, Jakarta. The research design uses a quantitative descriptive design, sampling technique using the purposive sampling used in this research were 50 persons. Data collection was carried out through interviews and questionnaires, interviews and psychological test. Data analysis used multiple linear regression. Based on the results of the research, it was concluded social support and self efficacy in patients breast cancer have affect the patients subjective well being. Based on the results of the research, it was concluded social support and self efficacy in patients breast cancer have affect the patients subjective well being, optimizing social support and increasing self-efficacy needs to be sought to improve psychological well-being related to body image patients.